2024
DOI: 10.1037/mac0000113
|View full text |Cite
|
Sign up to set email alerts
|

On the educational relevance of immediate judgment of learning reactivity: No effects of predicting one’s memory for general knowledge facts.

Abstract: Several studies revealed that predicting one's memory during learning has reactive effects on memory performance: making judgments of learning (JOLs) improved cued-recall performance for related word pairs and recognition memory for single words but impaired or did not impact cued recall for unrelated word pairs. Very little is known, however, about the generalizability of JOL reactivity to educationally relevant study materials and test conditions. The three experiments reported here examined whether making J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Another possible explanation for the divergent reactivity effects on learning of simple and complex materials is the natural difference between simple (e.g., word pairs and word lists) and complex (e.g., text passages and general knowledge facts) materials. As noted by Schäfer and Undorf (2023), word pairs and word lists used in many previous reactivity studies typically lack interitem relations (i.e., relations among different items), whereas knowledge points stated in text passages are always interrelated and mastery of these materials involves constructing relations among pieces of information (Rohrer et al 2020). Two recent studies consistently showed that although making JOLs reactively enhances item memory (i.e., memory of the item itself), it concurrently impairs interitem relational mem-ory (i.e., memory of interitem relations) (Zhao et al 2023).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Another possible explanation for the divergent reactivity effects on learning of simple and complex materials is the natural difference between simple (e.g., word pairs and word lists) and complex (e.g., text passages and general knowledge facts) materials. As noted by Schäfer and Undorf (2023), word pairs and word lists used in many previous reactivity studies typically lack interitem relations (i.e., relations among different items), whereas knowledge points stated in text passages are always interrelated and mastery of these materials involves constructing relations among pieces of information (Rohrer et al 2020). Two recent studies consistently showed that although making JOLs reactively enhances item memory (i.e., memory of the item itself), it concurrently impairs interitem relational mem-ory (i.e., memory of interitem relations) (Zhao et al 2023).…”
Section: Discussionmentioning
confidence: 75%
“…Besides Ariel et al (2021) and the current study, another recent study explored whether making JOLs reactively facilitates learning of another type of educationally representative material, that is, general knowledge facts (Schäfer and Undorf 2023). In the same line, Schäfer and Undorf (2023) found no reactivity effect of JOLs on learning of general knowledge facts. It is intriguing that making JOLs reactively enhances learning of simple materials, such as related word pairs (Witherby and Tauber 2017), word lists (Zhao et al 2022), and visual images (Shi et al 2023), but does not affect learning of complex materials such as text passages (Ariel et al 2021) and general knowledge facts (Schäfer and Undorf 2023).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In addition to the theoretical implications discussed previously, another reason researchers have been interested in JOL reactivity is because of the potential applied implications (e.g., Ariel et al 2021;Schäfer and Undorf 2023). Specifically, given that JOLs have been shown to improve memory in some contexts in laboratory studies, it is possible that they could also be used in educational settings to improve learning.…”
Section: Discussionmentioning
confidence: 99%
“…In the current investigation, we focus on the reactive effect of making immediate JOLs on memory performance. Such JOL reactivity has been investigated for a variety of materials, including single words (e.g., Begg et al 1989 ; Halamish 2018 ; Li et al 2022 ; Senkova and Otani 2021 ; Tauber and Rhodes 2012 ; Tekin and Roediger 2020 ; Yang et al 2015 ; Zechmeister and Shaughnessy 1980 ; Zhao et al 2022 ), word pairs (e.g., Arbuckle and Cuddy 1969 ; Chang and Brainerd 2023 ; DeYoung and Serra 2021 ; Dougherty et al 2005 , 2018 ; Halamish and Undorf 2022 ; Janes et al 2018 ; Kelemen and Weaver 1997 ; Maxwell and Huff 2022a , 2022b ; Mitchum et al 2016 ; Myers et al 2020 ; Rivers et al 2021 , 2023 ; Soderstrom et al 2015 ; Tauber and Witherby 2019 ; Witherby and Tauber 2017 ; Zhao et al 2023 ), pictures (e.g., Shi et al 2022 ; Sommer et al 1995 ), general knowledge facts (e.g., Schäfer and Undorf 2023 ), and educational texts (e.g., Ariel et al 2021 ; Dobson et al 2019 ; Ha and Lee 2023 ). This research has typically revealed a memory benefit (i.e., positive reactivity) for cued recall of pairs with a semantic relationship (e.g., coat – jacket ), positive reactivity for recognition of single words or pictures, no recall benefit for cued recall of unrelated word pairs (e.g., dog – spoon ), and mixed results for educational material.…”
Section: Introductionmentioning
confidence: 99%